2020
DOI: 10.15562/jdmfs.v5i2.1089
|View full text |Cite
|
Sign up to set email alerts
|

The difference of corrosion resistance between NiTi archwires and NiTi with additional cooper archwires in artificial saliva

Abstract: Objective: The aim of this experiment showed the difference of corrosion resistance between Nickel-Titanium (NiTi) archwire and NiTi archwire with additional cooper (NiTi-Cu) in artificial saliva. Material and Methods: This research was conducted in these laboratory experiments, immersed the NiTi archwires and NiTi-Cu archwires on artificial saliva at pH= 7 and incubated on 37°C, with the ratio of the archwire and the saliva was 0.02 gr: 1 ml during 1 day, 33 days and 66 days.Results: Corrosion resistances rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This result was in line with research by Senkutvan et al ,[ 25 ] which showed a significant increase in Ni ion release from CuNiTi archwires with three immersion periods (one, two, and three weeks) – the highest was in the third week. Habar and Tatengkeng[ 26 ] also did similar research using 33 and 66 days of immersion. Their result also displayed a significant increase over time.…”
Section: Discussionmentioning
confidence: 86%
“…This result was in line with research by Senkutvan et al ,[ 25 ] which showed a significant increase in Ni ion release from CuNiTi archwires with three immersion periods (one, two, and three weeks) – the highest was in the third week. Habar and Tatengkeng[ 26 ] also did similar research using 33 and 66 days of immersion. Their result also displayed a significant increase over time.…”
Section: Discussionmentioning
confidence: 86%
“…One of the electrolytes that play a role in releasing ions is chloride ion. Chloride can damage the oxide layer on the alloy surface, causing the release of ions [17]. Artificial saliva contains organic components in the form of proteins which can act as an electrolyte medium, thus triggering chemical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Kawat CuNiTi merupakan salah satu jenis kawat yang banyak digunakan pada peeawatan ortodonsia, jenis kawat ini merupakan pengembangan dari kawat NiTi dengan penambahan elemen copper untuk meningkatkan kualitas dari kawat. Pada umumnya kandungan kawat CuNiTi terdiri dari 42,99% titanium, 49,87% nikel, 0,50% kromium dan 5,64% copper [3]. Kawat CuNiTi memiliki beberapa kelebihan diantaranya, elastisitas yang lebih besar dan hysteresis yang lebih rendah yang memungkinkan penghasilan gaya konstan yang lebih lama selama deaktivasi yang menguntungkan untuk pergerakan gigi [4].…”
Section: Pendahuluanunclassified